Secure Routing Protocol for Integrated UMTS and WLAN Ad Hoc Networks - Shashank Tripathi; A. K. Jain (Institute of Advanced Engineering and Science, 2016)
The integrated UMTS and WLAN ad hoc networks are getting more and more popular as they hold substantial advantages by next generation networks. We introduce a new secure, robust routing protocol specifically designed for next generation technologies and evaluated its performance. The design of the SNAuth_SPERIPv2 secure routing protocol takes advantage to the integrated network, maintaining Quality of Service (QoS) under Wormhole Attack (WHA). This paper compares performance of newly developed secure routing protocol with other security schemes for CBR video streaming service under WHA.